EFFECTS OF PULMONARY REHABILITATION ON SYSTEMIC INFLAMMATION IN INDIVIDUALS WITH SEVERE ASTHMA - Silva, Naiara Moreira da; Moura-Maia, Meiry de Souza Moura Maia; Reis, Anamei Silva Reis; Paula-Vieira, Rosa Helena Ramos; Vieira-RP, Rodolfo de Paula (CIPEEX, 2025)
Introduction: Severe asthma is characterized by persistent inflammation, airway remodeling, and lung function limitation, with symptoms persisting despite pharmacological treatment. Pulmonary rehabilitation (PR), especially aerobic exercise, not only improves functional capacity and reduces dyspnea but also modulates systemic inflammation, including cytokines and other proteins, making it a promising complementary approach. Objectives: To evaluate the effects of PR on systemic levels of cytokines and anti-fibrotic proteins in individuals with severe asthma. Methods: The study included 21 patients with severe asthma, diagnosed according to GINA criteria and evaluated by a pulmonologist. Inclusion criteria considered the absence of comorbidities, ongoing pharmacological treatment for ≥6 months, and age between 20–60 years. Venous blood was collected for hematological analysis and quantification of pro-inflammatory mediators (IL-1beta, IL-5, IL-6, IL-13), anti-inflammatory mediators (IL-1ra, IL-10), pro-fibrotic proteins (VEGF, TSLP), and anti-fibrotic proteins (relaxin-3, klotho) using ELISA. Data were analyzed using GraphPad Prism 5.0, with normality assessed by the Kolmogorov-Smirnov test and paired and independent Student’s t-tests, considering p<0.05 as statistically significant.Results: PR significantly reduced the number of neutrophils (p=0.0114), lymphocytes (p=0.0319), and eosinophils (p=0.0154). No changes were observed in the number of monocytes (p=0.3996) and basophils (p=0.2666). Regarding pro-inflammatory cytokines, PR significantly reduced plasma levels of IL-1beta (p=0.0447), IL-5 (p=0.0234), IL-6 (p=0.005), and IL-13 (p=0.0370). Concerning anti-inflammatory proteins, PR significantly increased plasma levels of IL-1ra (p=0.0485), IL-10 (p=0.0080), and klotho (p=0.0023), as well as the anti-fibrotic proteins relaxin-1 (p=0.0027) and relaxin-3 (p=0.0040). PR also reduced plasma levels of the pro-fibrotic proteins TSLP (p=0.008) and VEGF (p=0.001).Conclusion: Pulmonary rehabilitation significantly reduces systemic inflammation in individuals with severe asthma by modulating pro- and anti-inflammatory mediators and pro- and anti-fibrotic proteins, suggesting an important role in controlling the progression of severe asthma.